2019
DOI: 10.1038/s41575-019-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in colorectal cancer: rationale, challenges and potential

Abstract: Following initial successes in melanoma treatment, immunotherapy has rapidly become established as a major treatment modality for multiple types of solid cancers, including a subset of colorectal cancers (CRCs). Two programmed cell death 1 (PD1)-blocking antibodies, pembrolizumab and nivolumab, have shown efficacy in patients with metastatic CRC that is mismatch-repair-deficient and microsatellite instability-high (dMMR-MSI-H), and have been granted accelerated FDA approval. In contrast to most other treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
1,091
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,262 publications
(1,106 citation statements)
references
References 141 publications
10
1,091
1
4
Order By: Relevance
“…In CRC, it is well known that tumour morphology, growth pattern and architecture hold important clues to differentiating biological subtypes with clinical impact (10). The composition of the tumour microenvironment is a key component determining the tumour progression and therapy response (11,12). Tumour and non-tumour tissue contribute to image information on the histological slide and to the consensus molecular classification (CMS) of CRC at the transcriptional level (13) CMS subgrouping shows a robust association with targetable alterations and may have potential to guide treatment allocation in clinical practice (1,13).…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, it is well known that tumour morphology, growth pattern and architecture hold important clues to differentiating biological subtypes with clinical impact (10). The composition of the tumour microenvironment is a key component determining the tumour progression and therapy response (11,12). Tumour and non-tumour tissue contribute to image information on the histological slide and to the consensus molecular classification (CMS) of CRC at the transcriptional level (13) CMS subgrouping shows a robust association with targetable alterations and may have potential to guide treatment allocation in clinical practice (1,13).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional therapies, including chemotherapy and radiation therapy, remain the first‐line treatment for most cancer patients. In recent years, tumor immunotherapy has shifted from adjuvant therapy to an important treatment modality with the breakthrough of checkpoint inhibitor immunotherapy …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tumor immunotherapy has shifted from adjuvant therapy to an important treatment modality with the breakthrough of checkpoint inhibitor immunotherapy. 1 Immune checkpoint blockade treatment can give patients an unprecedented long-lasting anti-tumor response. By far the most widely used immunotherapy in various solid tumors and hematological malignancies is cytotoxic T lymphocyteassociated antigen 4 (CTLA4) or programmed cell death protein 1 (PD-1)-PD-1 ligand 1 (PD-L1) inhibitor, known as immune checkpoint inhibitors (ICIs).…”
Section: Introductionmentioning
confidence: 99%
“…Many cancers encode mutation‐associated neoantigens (MANAs), which might be potential determinants of immune checkpoint blockades, like PD‐1/PD‐L1 blockades . MMR‐deficient cancers have large numbers of MANAs which would stimulate the immune response . Recent studies have demonstrated that dMMR could predict the response to PD‐1 inhibitor in 12 different kinds of solid tumors, including cholangio carcinoma, endometrial cancer, neuroendocrine carcinoma, and osteosarcoma and so on .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] MMR-deficient cancers have large numbers of MANAs which would stimulate the immune response. 8 Recent studies have demonstrated that dMMR could predict the response to PD-1 inhibitor in 12 different kinds of solid tumors, including cholangio carcinoma, endometrial cancer, neuroendocrine carcinoma, and osteosarcoma and so on. 9 Therefore, the evaluation of MSI and MMR deficiency has significance in predicting the response to PD-1/PD-L1 checkpoint blockades in various types of cancers.…”
Section: Introductionmentioning
confidence: 99%